The Mathnawî of Mawlâna Jalâladdîn-i Rûmî (2007) - Nicholson, Reynold A.; Kayadibi, Saim (Tablet Publication, 2007)
This universally well known book of Mawlana Jalaladdin Rumi's famous work Mathnawî consists of six volumes or books, however, after precise working on it, I simplified as well as translated the couplets which were left in Latin translation into English and in order to be carried easily and studied effectively, I combined the six volumes into one book. So it is formed as one book which contains of that six books. The Mathnawî contains the subjects of love, lover, soul (nafs), how to educate your self desires, deceptions, evils, reason, knowledge, persuading people to gain the eternal life and denying of one’s existence in order to affirm that of God, tolerance, peace, general Islamic teachings through a tale style. This new simplified version of Matnawî may give reader and researcher essential requirements of life guidance which is a much more organized and simplified copy of the Matnawî that provides a step to the spiritual and eternal journey who wants to reach a high spiritual stage of human beings. I hope that this new work brings blessings and full of success. I believe that effort must be from us, discretion is from the readers and of course divine guidance is from Allah (swt).